Super bloom : a novel - Tady, Megan (Zibby Books, 2023)
Massage therapist Joan Johnston works at an iconic Vermont spa, but she's deep in debt, burnt out, and grieving the death of her boyfriend. Spa guest Carmen Bronze, a hotheaded bestselling romance author, offers Joan a chance to pay off her debt by dishing spa secrets for Carmen's next novel. Sounds easy enough until Joan realizes she wants to write the story herself.